Is Complete Land Property Rights Increase Productivity of Rice Farming? - Adriansyah, Jefri; Gultom, Yohanna M. Lidya (BHUMI: Jurnal Agraria dan Pertanahan, 2023)
Abstract: This study examines how changes in the status of agricultural land property rights affects the productivity of rice farming, taking the case in Indonesia. By employing the two-period difference-in-differences (DiD) approach, we examine the productivity of 686 rice farming households that were covered in the IFLS longitudinal data panel survey in 2007 and 2014. IFLS itself is a survey with a sample that is considered to represent about 83 percent of the Indonesian population which was held in 13 provinces of the 34 existing provinces. The advantage of this research is the use of longitudinal data with observations on the same household and is a panel related to rice farming households. We find that changes in land property rights status from incomplete to complete property rights, has no effect on the productivity of rice farming, suggesting that to improve rice productivity, the government can not relying solely on land registration program. In Indonesia, land registration program solely implemented on land that is dispute free, therefore, there is no significant impact on creating maximization behaviour in input of production that can increase productivity. Keywords: Asset legality, difference-in-differences analysis, land status, maximization behavior transferability